Pembelajaran Naḥwu-Ṣarf di Pesantren dengan Pendekatan Interpretatif: Implikasi Teori Interpretasi Jorge JE Gracia dalam Pembelajaran Kitab Alfiyyah Ibn Mālik - Habib Maulana Maslahul Adi; Nur Romdlon Maslahul Adi (IAIN Madura, 2022)
This study aims to reveal and describe the reasons, processes, and implications of learning Naḥwu-Ṣarf from the book Alfiyyah Ibn Mālik with interpretive approach at Pondok Pesantren Al-Luqmaniyyah Yogyakarta. This study used a qualitative approach, where data were obtained through observation, interviews, and documentation techniques. Data analysis was carried out by reducing, interpreting, presenting, and drawing conclusions. Data testing is done through triangulation. The results of the study show that: (1) The reasons for practicing interpretive learning are because textual understanding of naẓm is the main paradigm of learning, as well as the content behind the textual meaning that is intriguing; (2) the process involves extracting the original meaning of the text, the original meaning intended by the author, extracting the implicit meaning behind textual understanding, and relating it to other things; and (3) It has implications for increasing the students’ interest in learning participation, as well as inculcating the knowledge values to students’ life.